The Influence of Opinion Leadership, Sales Promotion, and Perceived Quality on Oat Milk Purchase Intention - Janitrafia, Sabila Ratna (Universitas Nahdlatul Ulama Surabaya, 2025)
This research is analyzing the influence of opinion leadership, sales promotion and perceived quality on oat milk product purchase intention. This research used quantitative and purpose sampling method to gather data from 135 consumers of oat milk product who resided in South Tangerang City, Indonesia. The gathered data analyzed using SEM – PLS method. The results of this research is opinion leadership has positive influence on sales promotion, Opinion leadership and sales promotion has positive influence on perceived quality and purchase intention. However, perceived quality has not positive influence on purchase intention. The summary of this result is opinion leadership and sales promotion can be used by company as a tool for increasing consumer perceived quality and generate purchase intention.